Virtual simulation of a mechanical structure with 5DOF for induction hardening using Unity3D - Ionel-Alexandru, Gal; Luige, Vladareanu; Cang, Shuang (International Journal of Engineering and Technology, 2018)
In this paper we propose a mechanical structure with 5 degrees of freedom, designed to be used for induction hardening of metallic profiles which are used in building framed structures. All 5 joints of the proposed mechanical structure are prismatic, required to move a metallic profile through the inducer. The simulation was achieved using Unity3D software which provides the virtual environment needed for our purposes. To use the virtual simulation of the structure, we have had to build software components to help us gain access to the simulated components during the simulation. More components were added to implement the user interface and also the management backbone of the entire simulation. All of the software components which are used to interact with the mechanical system or its joints have been configured individually, supplying environment or physical variables for each component.Â Â